Diet composition of the Italian roe deer (Capreolus capreolus italicus) (Mammalia: Cervidae) from two protected areas. Issue 1 (1st January 2017) - Freschi, P.; Fascetti, S.; Riga, F.; Cosentino, C.; Rizzardini, G.; Musto, M.
Abstract: The Italian roe deer is classified as â€œvulnerableâ€ in the International Union for Conservation of Nature Red List of Threatened Species, as the few specimens of this endemism may have a high risk of extinction. Conservation efforts for the Italian roe deer cannot prescind from the study of the feeding habits of the taxon. Therefore, in the present study, the spring diet composition of the Italian roe deer from two protected areas was estimated by using the micro-histological technique of faecal analysis. Univariate measures of alpha and beta diversity were computed to assess spatial differences in diet composition between the sites. A total of 79 different species of plants were identified, with few species (mainly woody plants) comprising over a quarter of the diet. The most consumed species were Rubia peregrina, Quercus suber and Osyris alba in Site 1, and Q. cerris, Carpinus betulus and Crataegus monogyna in Site 2. Alpha diversity analysis showed that diet composition was quite rich and diverse in both sites, with nearly all the shared species eaten to an equal extent. Moreover, the values of alpha diversity indices were not significantly different between the sites. The degree of dietary overlap ranged from â€œlowâ€ to â€œhighâ€, as most of the identified plants were unshared, whereas the consumption of some shared plants differed between the sites. In conclusion, our results showed that that this subspecies of Capreolus is capable of exhibiting both a generalist and an opportunistic behaviour in relation of food resource availability.